Remedial Metaphor: Pedagogical Frye. - Wilson, Jean (University of Toronto Quarterly)
In his ongoing inquiry into the social value of literary study, Frye not only critiques perceptions of the humanities as ornamental rather than functional, but also complicates common notions of relevance and practicality. He resists, moreover, conventional distinctions between the arts and the sciences, and recognizes that a wide range of disciplines, from 'philology' to 'physics,' constitute the liberal arts. As he articulates it, what unites the scientist and the humanist is social, a matter of 'the practical intelligence,' which derives its authority from an informing vision of society. Frye's writings suggest that such capacity can be developed through pedagogical approaches that enable freedom from ready-made language and thought and access to 'the real world of human constructive power.' His literary and educational theory offers a perspective from which we might confront the challenges both of teaching literature in the twenty-first century and of fashioning forward-thinking liberal arts programs and interdisciplinary projects.